African American Community Leaders' Policy Recommendations for Reducing Racial Disparities in HIV Infection, Treatment, and Care: Results From a Community-Based Participatory Research Project in Philadelphia, Pennsylvania. Issue 1 (January 2015) - Nunn, Amy; Sanders, Julia; Carson, Lee; Thomas, Gladys; Cornwall, Alexandra; Towey, Caitlin; Lee, Hwajin; Tasco, Marian; Shabazz-El, Waheedah; Yolken, Annajane; Smith, Tyrone; Bell, Gary; et al.
African Americans account for 45% of new HIV infections in the United States. Little empirical research investigates African American community leaders' normative recommendations for addressing these disparities. Philadelphia's HIV infection rate is 5 times the national average, nearly 70% of new infections are among African Americans, and 2% of African Americans in Philadelphia are living with HIV/AIDS. Using a community-based participatory research approach, we convened focus groups among 52 African American community leaders from diverse backgrounds to solicit normative recommendations for reducing Philadelphia's racial disparities in HIV infection. Leaders recommended that (a) Philadelphia's city government should raise awareness about HIV/AIDS with media campaigns featuring local leaders, (b) local HIV-prevention interventions should address social and structural factors influencing HIV risks rather than focus exclusively on mode of HIV transmission, (c) resources should be distributed to the most heavily affected neighborhoods of Philadelphia, and (d) faith institutions should play a critical role in HIV testing, treatment, and prevention efforts. We developed a policy memo highlighting these normative recommendations for how to enhance local HIV prevention policy. This policy memo led to Philadelphia City Council hearings about HIV/AIDS in October 2010 and subsequently informed local HIV/AIDS prevention policy and development of local HIV prevention interventions. This community-based participatory research case study offers important lessons for effectively engaging community leaders in research to promote HIV/AIDS policy change.